3
- x 6 = 4
4
Mary has 6 cakes, she gives 3/4 of the cakes away. How many cakes does Mary have?
<span>The method of solving "by substitution" works by solving one of the equations (you choose which one) for one of the variables (you choose which one), and then plugging this back into the other equation, "substituting" for the chosen variable and solving for the other. Then you back-solve for the first variable.</span>
X:2+(105-275:11):4=28
X:2+(105-25):4=28
X:2+80:4=28
X:2+20=28
X:2=28-20
X:2=8
X=8×2
X=16
1) The expressions are not equivalent. When you expand and multiply 2(x + 3) it becomes 2x + 6. This is not equal to 3x + 5
2) They are equivalent. Again, expand and multiply the second expression. 2(3n + 4) becomes 6n + 8. This makes both sides equal.
3) They are equivalent. In the parentheses, you are adding 3 y's and a 2. This gives you 3y + 2. Now add the additional 3y that follows the closed parentheses. You'll have 6y + 2. Now both sides are equivalent.
3(2)+2(3)=12 <<<< is the answer! :)